FACTORS AFFECTING VEGETABLE BUSINESS PRODUCTIVITY IN AFA-AFA KELURAHAN, TIDORE CITY, ISLANDS - Nurdiyanawati Djumadil; Yunus Syafie (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the factors that influence the effectiveness of farmer groups in the development of horticultural crops, especially vegetables in Afa-Afa Village, Tidore Islands City, with the consideration that; Afa-Afa Village, North Tidore District, Tidore Islands City, is one of the centers for horticultural crops (vegetables), Farmers group members are active in farming, Have fertile land. Data collection techniques were carried out through observation, interviews, documentation and recording. Testing the questionnaire using the test of vekiditas and reliability. Data analysis using Multiple Linear Regression. The results showed that the characteristics of vegetable farming farmers in Afa-Afa village based on experience in farming as a farmer group ranged from 5 to 10 years. while the level of knowledge of farmer groups in Afa-Afa Village, North Tidore District, Tidore Islands City shows moderate to high criteria with the same percentage, namely 50% (high) and 50% (medium). Testing the effectiveness of farmer groups simultaneously there are three variables that influence the level of experience, the level of willingness to share knowledge and the variable level of income. The magnitude of the contribution of all these variables affect the effectiveness of the farmer group, which is Rp. 80.1%. Partially, only two variables have a significant effect, namely the variable level of willingness to share knowledge and the variable level of income in the development of horticultural crops, especially vegetables. While the experience level variable has no significant effect.